(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
As a result of the National Nature Park "Oleshkivski Pisky" microbiota study, 112 species of fungi and fungi-like protists were found: 18 species are slime molds, 1 – Zygomycota, 32 – Ascomycota and 61 – Basidiomycota representatives. Among them 14 species are fungicolous, 2 – myxomyceticulous and 1 – lichenicolous. Fungicolous species Hypomyces albidus Rehm in anamorphous stage Cladobotryum sphaerocephalum (Berk.) Rogerson et Samuels and myxomycete Amaurochaete tubulina (Alb. et Schwein.) T. Macbr. are registered in Ukraine for the first time. An interesting record is Patellaria crassispora H.- O. Baral, nomen provisum, which was also not known in Ukraine till now. We assume that ascigenous sporification of Mycosphaerella sp., found by us on overwintered needles of Pinus palassiana D. Don, probably is a still undescribed teleomorph of Dothistroma pini Hulbary. Slime mould Stemonitopsis microspora (Lister) Nann.-Bremek. registered in the steppe zone of Ukraine for the first time.